Study on Oxidation of 1,2-Dipropyldisulfane in Oxidative Desulfurization - Song, Y.Z. (Asian Journal of Chemistry, 2015)
DFT calculations were performed for calculation of standard electrode potential for 1,2-dipropyldisulfane sulfone/2-dipropyldisulfane. The electrochemical behaviour of 1,2-dipropyldisulfane at gold electrode was investigated by cyclic voltammety and the results showed that experimental standard electrode potential for 1,2-dipropyldisulfane sulfone/1,2-dipropyldisulfane is 1.111 V, which is consistent with that of 1.067 V at B3LYP/6-31++g(d, p)-PCM level. The front orbit theory and Mülliken charges of moleculer explain well on the oxidation of 1,2-dipropyldisulfane in oxidative desulfurization. According to equilibrium theory the experimental equilibrium constant in the oxidative desulfurization system of 1,2-dipropyldisulfane/H2O2, is 2.27 × 1089, which is consistent with the theoretical equilibrium constant is 2.10 × 1095 at B3LYP/6-31++g(d, p)-PCM level, indicating that 1,2-dipropyldisulfane can be oxidized by H2O2.